2019
DOI: 10.1002/lary.28258
|View full text |Cite
|
Sign up to set email alerts
|

Retronasal olfactory function in patients with smell loss but subjectively normal flavor perception

Abstract: Objectives The human sense of smell constitutes the main part of flavor perception. Typically, patients with loss of olfactory function complain of diminished perception during eating and drinking. However, some patients with smell loss still report normal enjoyment of foods. The aim of the present study was to compare orthonasal and retronasal olfactory function in patients with non‐sinonasal smell loss and subjectively normal flavor perception. Methods Nineteen patients (mean age [range] 52.0 [8–83 years]) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 37 publications
2
45
0
3
Order By: Relevance
“…Retronasal olfactory function was tested using the Candy Smell Test (CST) [21,22]. Originally validated in a 23-item version [21], we applied a 27-item version in all subjects [15,23]. For this version, less-identifiable aromas of the original items [21] were removed (three aromas: passion fruit, strawberry and kiwi) and others introduced (seven aromas, see Table 1.)…”
Section: Olfactory Testsmentioning
confidence: 99%
“…Retronasal olfactory function was tested using the Candy Smell Test (CST) [21,22]. Originally validated in a 23-item version [21], we applied a 27-item version in all subjects [15,23]. For this version, less-identifiable aromas of the original items [21] were removed (three aromas: passion fruit, strawberry and kiwi) and others introduced (seven aromas, see Table 1.)…”
Section: Olfactory Testsmentioning
confidence: 99%
“…Olfaction plays a critical role in various aspects of daily life so olfactory dysfunction (OD) results in a significant loss of information, such as sensory stimulation and environmental cues (1)(2)(3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
“…16 Nevertheless, two recent studies show a strong correlation between orthonasal and retronasal measurements in chronic rhinosinusitis, 23,24 although patients with anosmia were shown to identify certain retronasal odors more often than expected. 24 On the other hand, Liu et al found patients with non-sinogenic orthonasal smell deficit claiming normal flavor perception, to be also retronasaly dysosmic 17 ; therefore, being unaware of their retronasal deficit. They postulated that self-reports of flavor perception are unreliable and offered as an explaining mechanism memory retrieving of flavor patterns from previous experiences.…”
Section: Discussionmentioning
confidence: 99%